2000
DOI: 10.1046/j.1365-2869.2000.00195.x
|View full text |Cite
|
Sign up to set email alerts
|

The ability to self‐monitor performance when fatigued

Abstract: The present study aimed to systematically investigate the effects of elevated fatigue levels on the ability to self‐monitor performance. Eighteen participants, aged 19–26 y, remained awake for a period of 28 h. Neurobehavioural performance was measured at hourly intervals using four tests from a standardized computer test battery. From these four tests, six measures of performance were obtained: grammatical reasoning (accuracy and response latency); vigilance (accuracy and response latency); simple sensory com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
66
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(79 citation statements)
references
References 17 publications
11
66
1
1
Order By: Relevance
“…The participants' true feelings of alertness may have been masked by an 'end-of-shift' effect which has been observed in other studies 21,29) . This is evident when comparing the post shift alertness levels for the afternoon and night shifts in Fig.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The participants' true feelings of alertness may have been masked by an 'end-of-shift' effect which has been observed in other studies 21,29) . This is evident when comparing the post shift alertness levels for the afternoon and night shifts in Fig.…”
Section: Discussionmentioning
confidence: 63%
“…A possible reason for this result is that the alertness scales used (SamnPerelli and Visual Analogue Scales) may not have been sensitive enough to detect changes in alertness caused by the prior break length. However, recent publications have reported subjective estimates to have moderate to strong correlations with objective performance, especially at the end of a testing period 28,29) , refuting this argument. The reported lack of significance may instead be caused by limited testing opportunity.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have identified that healthcare professionals have difficulty in assessing their own levels of fatigue. [73,74] Thus, interventions should be introduced in healthcare organizations which include educational program such as Fatigue Countermeasure, [75] and schedule alterations which allow for information regarding the symptoms of fatigue, sleep hygiene measures, shift work and its adverse effects to be implemented. Furthermore, the hospital process could help in preventing fatigue among nurses by careful scheduling.…”
Section: Discussionmentioning
confidence: 99%
“…It is in addressing this question that scientific research can have an important impact, by assessing how well people can assess their impairment, what factors they take into account in doing so, and how well they can use this information to engage in appropriate behaviours. Research has shown that for situations involving a single period of acute sleep deprivation using laboratory tasks individuals have an accurate perception of their performance 26,27) . However, during simulated night shift work, the ability to predict performance was moderate at best 28) .…”
Section: Mens Reamentioning
confidence: 99%
“…Thus a person who has 2 h of sleep in the prior 24 would not be covered by the law, and neither would the driver who causes serious injury but not death. Furthermore it overlooks the difficulty that individuals have when measuring their objective performance when fatigued [26][27][28][29] giving rise to potential complaints that people would not have a fair opportunity to comply with a law drafted in this manner (See 41) for a discussion of the application of the fair opportunity principle to involuntariness).…”
Section: A Way Forward?mentioning
confidence: 99%